Inquiry-Based Learning for Improving Student Learning Outcomes: Literature Review - Seftiani Utami; Sri Sundari (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2019)
The learning process has entered the 21st century and shifted from Teacher Center Learning (TCL) to Student Center Learning (SCL). Therefore, to improve student learning achievement and activity, innovative learning models are needed to provide more active learning opportunities for students in the learning process. There are a number of innovative learning models, one of which can improve student achievement and activity is inquiry-based learning. It would be better for students to discuss lessons or try to learn the material first, then present the results in front of the class and discuss with other students. Thus, the learning process becomes more active and dynamic with the guidance and direction of the lecturer. This literature review aims to determine the influence of the application of inquiry learning in improving student learning outcomes. The design used is a literature review, articles are collected using the database proquest, google scholar and Science Direct with the keywords “inquiry based learning model” AND “learning outcomes”. The criteria for the articles used are those published in 2014-2018. Based on thirteen articles collected, the results showed that ten articles showed that inquiry learning improved student learning outcomes while the other three did not influence student learning outcomes, but could increase learning motivation. The inquiry-based learning involves students directly and actively in the learning process so that learning has a significant effect on improving learning outcomes.